2014
DOI: 10.1002/fsn3.113
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the survival of exogenous plant microRNA in mice

Abstract: MicroRNAs (miRNAs), a class of small RNAs, are important molecules that influence several developmental processes and regulate RNA interference (RNAi), and are abundant in animals, plants, and plant tissues that are traditionally consumed in the diet. The survival of plant small RNAs from the diet in animals, however, remains unclear, and the persistence of miRNAs from dietary plants in the animal gastrointestinal (GI) tract is still under debate. In this study, ICR mice were fed plant total RNAs in quantities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 32 publications
4
113
0
1
Order By: Relevance
“…Expression of immune-modulatory miRNAs, especially miR-146a, has been determined in different diabetic complications, [48][49][50][51][52] including DN. 49,[53][54][55] While some studies have shown lower miR-146a expression during DN, 49 others have shown higher expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of immune-modulatory miRNAs, especially miR-146a, has been determined in different diabetic complications, [48][49][50][51][52] including DN. 49,[53][54][55] While some studies have shown lower miR-146a expression during DN, 49 others have shown higher expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the expression of miR-146a is very sensitive to levels of proinflammatory mediators 56 and may follow a temporal or circadian pattern 51 and that, depending on the inflammation levels and tissues tested, miR-146a expression may show significant variations. Of note, the extent of miR-146a induction at 16 weeks after diabetes was much lower than at 7 weeks, suggesting a progressive decline of this "protective" miRNA during the development of DN.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been argued that the inability to detect the uptake of plant miRNAs was due to only looking at a few selected miRNAs rather than using sequencing to screen for all plant miRNAs. Furthermore, the cross-kingdom presence and potential function of plant miRNAs in mammals are supported by independent studies from only two different labs in the past three years, highlighting the need for further verification [22,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA-containing foods are found in animals and plant resources [68,69] [34,72]. First, some of the plant miRNAs in human serum are genuine plant miRNAs.…”
Section: Plant Mirnasmentioning
confidence: 99%